2018
DOI: 10.1002/da.22723
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD) as per ICD-11 proposals: A population study in Israel

Abstract: These results partially support the factorial validity and strongly support the discriminant validity of the ICD-11 proposals for PTSD and CPTSD in a nationally representative sample using a disorder-specific measure; findings also supported the international applicability of these diagnoses. Further research is required to determine the prevalence rates of PTSD and CPTSD in national representative samples across different countries and explore the predictive utility of different types of traumatic life events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
150
9
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 174 publications
(195 citation statements)
references
References 53 publications
31
150
9
5
Order By: Relevance
“…However, an important difference between these studies and the current study is that the AD factor was estimated as a unidimensional construct and the study conducted by Silove and colleagues did not estimate a correlated first-order model. The current results supporting that affect dysregulation is better represented as two correlated but distinct factors ( r  = 0.66) are consistent with a study conducted on a community sample of Israelis, which found that a correlated first-order seven-factor model with hyper- and hypo-activation modelled as correlated but distinct constructs was the best fitting model (Ben-Ezra et al, 2018). …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, an important difference between these studies and the current study is that the AD factor was estimated as a unidimensional construct and the study conducted by Silove and colleagues did not estimate a correlated first-order model. The current results supporting that affect dysregulation is better represented as two correlated but distinct factors ( r  = 0.66) are consistent with a study conducted on a community sample of Israelis, which found that a correlated first-order seven-factor model with hyper- and hypo-activation modelled as correlated but distinct constructs was the best fitting model (Ben-Ezra et al, 2018). …”
Section: Discussionsupporting
confidence: 91%
“…This finding is considerably higher than reported by Silove et al (2017) and Ben-Ezra et al (2018), with CPTSD prevalence estimates of 3% and 2.6%, respectively, but lower than a multicultural refugee sample of whom 32.8% met the CPTSD criteria (Nickerson et al, 2016). However, given the context of the traumatic exposure that these individuals faced during their childhood, this finding is not surprising.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations